PENGARUH FASILITAS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL LEMBAGA PERMASYARAKATAN KELAS IIB KOTA PARIAMAN - Budi Yanti; Henny Sjafitri (Ensiklopedia of Journal, 2021)
The purpose of this study was to determine and analyze the effect of work facilities on work discipline partially and simultaneously on the Performance of Civil Servants of Class IIB Pariaman Penitentiary. The research method used is descriptive quantitative. The sampling technique used is the total sampling technique, so that from the population there is a sample of 68 respondents, the data collection methods used are observation, questionnaires and library studies. The data analysis technique used is multiple linear regression, t test, F test and coefficient of determination. +0.032X1+0.596X2+e. The results of the t-test carried out showed that the work facilities variable had no significant effect on the Performance of Civil Servants at the Class IIB Penitentiary in Pariaman City with a significant value of 0.780 > 0.005 and tcount < ttable of 0.280 < 1.668, the Work Discipline variable had a significant effect on the Performance of Civil Servants. Civilian Penitentiary Class IIB Pariaman City with a significant value of 0.000 < 0.005 and tcount > ttable of 6.768 > 1.668. The results of the F test prove that the variables of work facilities, and work discipline simultaneously have a significant effect on the Performance of Civil Servants at the Class IIB Pariaman Penitentiary, this can be proven by the value of Fcount > Ftable or 22,982 > 3.14 and a significant level of 0.000 < 0.05. The result of the coefficient of determination is 39.6%, while the remaining 60.4% is explained by other variables not examined in this study.